Whole-cell calcium current in guinea-pig ventricular myocytes dialysed with guanine nucleotides. - Shuba, Y M (1990)
1. Whole-cell calcium current (ICa) was recorded in guinea-pig ventricular myocytes superfused with Na+,K(+)-free solution and dialysed with a substrate-free solution (minimum intracellular solution, MICS). A dual tight-seal pipette method was often used to permit pressure-enhanced dialysis of a test solution after a given pre-dialysis. 2. In dual-pipette experiments, test dialysates contained 100 mM-GTP-gamma-S (guanosine 5'-O-(3-thiotriphosphate] or 100 microM-GMP-PNP (guanyl-5'-imidodiphosphate). These non-hydrolysable analogues of guanosine triphosphate (GTP) enhanced ICa amplitude (+ 10 mV) by 20-40%. Dialysates containing 100 microM-GTP or GDP-beta-S (guanosine 5'-O-(2-thiodiphosphate] were ineffective, and pre-dialysis with GDP-beta-S blocked stimulation by GTP-gamma-S. 3. Non-hydrolysable GTP analogues slowed the inactivation of ICa and shifted the voltage eliciting maximum ICa by 5-10 mV in the negative direction. 4. ICa enhancement by GTP analogues was attributed to the activation of three GTP-binding regulatory (G) proteins (Gi, Gp and Gs). In single-pipette experiments, the inactivation of Gi by pre-treatment with pertussis toxin did not block enhancement, and a Gp-activating regimen (external acetylcholine-internal GTP) was without effect. Thus, it is probable that the effects of GTP analogues on ICa were primarily mediated by Gs activation. 5. PI-MICS dialysates contained phosphorylation-pathway inhibitors and were used to inhibit Ca2+ channel phosphorylation via the adenyl cyclase pathway. These were deemed effective since forskolin (1-5 microM) doubled ICa during control dialysis but was without effect after 8 min PI-MICS dialysis. However, 0.1 microM-isoprenaline increased ICa by 35% in myocytes totally unresponsive to forskolin, suggesting that beta-adrenergic receptor occupation can stimulate ICa even when the phosphorylation pathway is blocked. 6. After prolonged dialysis of myocytes with PI-MICS, ICa was still enhanced by pressure-assisted dialysis of 100 microM-GTP-gamma-S or GMP-PNP. We conclude that activated Gs has a direct effect on cardiac Ca2+ channels.